An evaluation of half-cut technique for microwave-photonic access-point antenna miniaturization - Ngah, R. (2011)
A microstrip-fed broadband printed monopole antenna covering 1.7 - 6.0 GHz is miniaturized using half-cut technique, and arranged in pair for uplink/downlink microwave-photonic access point. This paper discusses the effect of the miniaturization to S11 and radiation pattern of individual antenna, and also the best choice of antenna pair, ground-plane type, and total width of the access point.